Organic chemistry - Solomons, T. W. Graham; Fryhle, Craig B.; Snyder, S. A. (Scott A.) (Hoboken, NJ : Wiley, 2022)
"What is your favorite organic molecule? This is a question that may not have crossed your mind, but we aim to change that. There are many good reasons to have a favorite molecule (or several!), given their impact on the world. Indeed, some have started wars, others have sustained and extended human life, and many have dramatically changed the mores of modern society. One choice for a favorite organic molecule could be vancomycin, an antibiotic of last resort that is featured on the cover of our book. Molecules like vancomycin, aspirin, penicillin, and many other medicinally active compounds have saved the lives of millions over the course of the past century. Others like quinine, the first treatment for malaria, were so scarce that human conflict arose over its supply. New and Updated Information about the Relevance of Organic Chemistry The applications of chemistry are often what turn a student on to its value and a desire to learn it. Our text has always been strong in drawing the connections between chemistry and life and we continue to build on it. We have added new material on several topics, including the relevance of intermolecular forces in the immune response and vaccines like those for Covid-19, the chemistry of breathing (carbonic anhydrase), how conjugation and complexation affects the color of lobsters, and how biodegradable polymers are used to stabilize vaccines and pharmaceuticals."--
Includes index
Keywords: Chemistry, Organic -- Textbooks; Textbooks